NAIRAS Model Run‐On‐Request Service at CCMC - C. J. Mertens; G. P. Gronoff; Y. Zheng; M. Petrenko; J. Buhler; D. Phoenix; E. Willis; I. Jun; J. Minow (Space Weather)
Abstract The Nowcast of Aerospace Ionizing RAdiation System (NAIRAS) version 3 model is available to the community through the Community Coordinated Modeling Center run‐on‐request (RoR) service. The RoR capability allows the user to run the NAIRAS model for customized applications and time‐periods using two run options. The global dosimetric run option mirrors the execution of the real‐time NAIRAS run mode. This class of run option capability provides global context and situational awareness of the atmospheric ionizing radiation environment. The flight trajectory run option allows the user to upload an aircraft, balloon, or spaceflight trajectory file. This class of run option allows detailed human radiation flight exposure characterization, detailed comparisons to onboard dosimeters, and the assessment of single event effects (SEE) in aircraft and spacecraft electronic systems. The model output includes dosimetric quantities, differential and integral flux, and fluence quantities. The flux and fluence quantities are a new feature in version 3 for the assessment of SEE. The trajectory run option and the extension of the model domain to the space environment is also a new feature in version 3.